El entrenamiento como base de la formación actoral - Araque Osorio, Carlos (CALLE14: revista de investigación en el campo del arte, 2011)
The text presents a reflection on the actor’s training and its implications, virtues and contributions to the professional formation of actors. It starts from the experience that the author has assimilated as teacher and director, but mainly as an active actor, that appeals to his body as a work tool. From this perspective, the relationships between exercise, system and rehearsal are analyzed. Performance is not an esoteric and mystic act propitiated by the gods, it is a work that requires preparation, dedication and conscious inquiry. The actor or the actress that are unable to train in solitude, cannot contribute to a group, perhaps, this should be done without losing the perspective that theater is a collective act, in which communication plays an important role. For this reason, is fundamental to know how it is expressed, how it is signified and how a communication is begun between the actor and the spectator.